Egipto y el Egeo a comienzos de la XVIII dinastía : una visión de sus relaciones, antecedentes e influencia iconográfica - Vivas Sainz, Inmaculada, (BAR International Series ;, 2013)
"This study is focused on the relations between Egypt and the Aegean during the early XVIIIth Dynasty, a period of close contact between these two regions. The discovery of Minoan wall paintings decorating a palace complex at Tell el Dab'a (Avaris) was the starting point for this research which reviews the evidence concerning the relations between Egyptians and Minoans especially during the beginning of the New Kingdom, but sometimes also looking at the evidence from previous periods. This contact brought together a mutual influence on artistic and cultural matters, which has its best evidence on the Minoan wall paintings decorating a Thutmoside palace complex in Egypt."--Publisher's web site.